2017
DOI: 10.5897/ajb2017.16016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plant-growth promoting properties of Gluconacetobacter diazotrophicus and Gluconacetobacter sacchari isolated from sugarcane and tomato in West Central region of Colombia

Abstract: The genus Gluconacetobacter comprises different species with agricultural and industrial importance. This study aims at determining the presence of Gluconacetobacter diazotrophicus and Gluconacetobacter sacchari in sugarcane and tomato crops considering their potential biotechnological applications. Bacteria were isolated from roots, stems and leaf tissues and identified using phenotypic and biochemical evaluations, and molecular and phylogenetic analyses. Isolates were characterized by the production of indol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Sugarcane is able to associate with a great diversity of diazotrophic plant growth-promoting bacteria, including species of the genera Azospirillum (Reis Junior et al 2000; Tejera et al 2005), Azotobacter (Tejera et al 2005), Burkholderia (Perin et al 2006; Antonio et al 2016; Silva et al 2016; Leite et al 2018a, b), Herbaspirillum (Baldani et al 1996; Reis Junior et al 2000), Pantoeae (Taulé et al 2012; Fischer et al 2012, Silva et al 2016), and the species Gluconacetobacter diazotrophicus (basonym Acetobacter diazotrophicus ) (Cavalcante and Döbereiner 1988; Munõz-Rojas and Caballero-Mellado 2003; Restrepo et al 2017), among others.…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…Sugarcane is able to associate with a great diversity of diazotrophic plant growth-promoting bacteria, including species of the genera Azospirillum (Reis Junior et al 2000; Tejera et al 2005), Azotobacter (Tejera et al 2005), Burkholderia (Perin et al 2006; Antonio et al 2016; Silva et al 2016; Leite et al 2018a, b), Herbaspirillum (Baldani et al 1996; Reis Junior et al 2000), Pantoeae (Taulé et al 2012; Fischer et al 2012, Silva et al 2016), and the species Gluconacetobacter diazotrophicus (basonym Acetobacter diazotrophicus ) (Cavalcante and Döbereiner 1988; Munõz-Rojas and Caballero-Mellado 2003; Restrepo et al 2017), among others.…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…In this way, it was shown that G. diazotrophicus exhibits plant growth-promoting properties not only in crops such as sugarcane (for which commercial preparations already exist) but also in economically important vegetable crops. Te carrot crop growth promotion is based on the special characteristics of G. diazotrophicus already demonstrated in a previous work by Restrepo et al [8]: biological nitrogen fxation thanks to its nitrogenase activity, phosphorus solubilization, and production of indole compounds. Te results obtained will contribute to the development of a novel microbial inoculant for vegetables under agroecological conditions in tropical areas.…”
Section: Discussionmentioning
confidence: 90%
“…Te standard strain G. diazotrophicus ATCC 49037 and the native isolate of G. diazotrophicus GIBI029 recovered from sugarcane [8] were used as inoculants, which were multiplied in modifed DYGS media [14] and LGI-P [15]. Te production of the inoculum and the liquid preparation were carried out in three stages.…”
Section: G Diazotrophicus Suspensionmentioning
confidence: 99%
See 1 more Smart Citation